Complex Orthodontic Approach with Esthetic Filler Modeling: Evaluation of Cephalometric and Photometric Results in Adult Patients with Sagittal Malocclusions - Kutsyuk Т. (Actual Dentistry, 2025)
Introduction. Sagittal malocclusions significantly impact the function of the dentoalveolar system and facial aesthetics, limiting orthodontic correction possibilities in adults. Achieving an ideal soft tissue profile often remains a challenge. Recently, the combination of orthodontic treatment with dermal filler injections has gained relevance for enhancing facial aesthetics. However, there’s insufficient systemic research comparing the effectiveness of exclusive orthodontic therapy and the combined approach, particularly regarding gender differences in soft tissue response. Aim: to evaluate the effectiveness of complex orthodontic treatment with esthetic fillers compared to monotherapy in adult patients with dentoalveolar and skeletal sagittal malocclusions. Material and Methods. We treated 173 adult patients with sagittal malocclusions, divided into two groups: Group A (n = 92) received orthodontic treatment supplemented with dermal filler injections, and Group B (n = 81) received orthodontic treatment only. Treatment effectiveness was assessed using cephalometric (TRG) and photometric analysis with statistical analysis (p < 0.05), with a particular focus on gender differences. Results. In patients with dentoalveolar anomalies, orthodontic treatment improved skeletal parameters through dentoalveolar compensation. Combined treatment significantly enhanced the esthetic facial profile in dentoalveolar forms, especially in women. For skeletal anomalies, the combined approach provided significantly better results in both cephalometric and photometric parameters, harmonizing the profile. The effect was more pronounced in women and in cases of distal occlusion. Conclusion. Combined therapy is a priority for achieving the maximum esthetic result in adult patients with horizontal malocclusions.